Dielectric properties of lanthanum lead cobalt titanium oxide (La1−xPbx) (Co1−xTix)03 (0.50 ≦ x ≦ 0.90) - Parkash O.; Prasad Ch.D.; Kumar D. (My University, 2025)
Dielectric properties of the system (La1−xPbx) (Co1−xTixO3 (0.50 ≦ x ≦ 0.90) are investigated as a function of temperature and frequency. All the samples exhibit diffuse phase transitions in the variation of their dielectric constant, ε, as a function of temperature. The variation of ε with temperature can be expressed by a quadratic law of the type ε−1 = ε max−1 + C(T – Tc)2 both above as well as below Tc over a considerable range of temperature where Tc is the temperature where ε shows the peak value εmax and C is a constant. Dielectric parameters show a pronounced frequency dependence near Tc. This points to the contribution of relaxation polarisation to the observed dielectric behaviour. The observed dielectric behaviour is interpreted on the basis of microscopic chemical inhomogeneities present in the samples. Copyright © 1988 WILEY‐VCH Verlag GmbH & Co. KGaA